Marketing Strategy in Increasing Consumer Buying Interest at Garuda Restaurant: (Case Study at Garuda Restaurant Branch) - Surya Kumar; Yuni Syahputri; Jafar Syahbuddin Ritonga; Hesti Sabrina (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This research aims to determine marketing strategies through SWOT analysis with a focus on segmentation, market position, targeting and marketing mix, which aims to increase consumer buying interest at Restaurant Garuda. The research results show that Restaurant Garuda implements various marketing mix strategies that influence the SWOT analysis, placing it in quadrant I (SO quadrant). This indicates a successful implementation of the odds and profits strategy, although with a slight difference of 2.4:2.95. Garuda Restaurant emphasizes the aspects of price, product, location and physical form of the building as the main factors that stimulate consumers' buying interest to try and remain loyal to their products. To maintain and increase consumer buying interest, it is recommended that Restaurant Garuda adopt product development strategies, improve brand image and maintain price stability. By implementing these strategies, it is hoped that Restaurant Garuda can maintain and increase their market share and customer satisfaction.